Narrativas "positivas”: vivências e experiências de professores portadores do HIV - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
HIV (Human Immunodeficiency Virus) is a virus that and modify the immune system, enhancing the risk of occurrence and the impact of other infections and diseases. Without a treatment, it progresses to AIDS (Acquired Immunodeficiency Syndrome), a communicable and lethal disease, for which there is not, until now, any healing medicine or prophylactic vaccine. The contamination, far from being restricted to social groups, reaches all society, without distinction of race, social class, religious creed, social or professional position. At this point, education professionals do not escape this reality. Thus, the objective of the research is to unveil the living and teaching experiences experienced by teachers with HIV in the educational field. The methodological design is based on the phenomenological method (CASTRO, 2014; BICUDO, 2011; MOREIRA), using the qualitative approach (BICUDO, 2011; BAUER, 2002; FLICK, 2009) and exploratory research (GIL, 2002), having as procedure the empirical bibliographic research using the narrative interview (auto) biographical as instrument of data collection (SOUZA, 2016; CASTRO, 2014). The theoretical contribution contemplates the situation of disease due to HIV infection, as well as the arising of stigmas and prejudices that the disease brings (PERETTI; SOUZA, 2014). The results enabled to perceive that education, as a formative and instructional social process, induces to silence, making it impossible for people to resignify their experiences before the world (SOUZA, 2016). With this, the process of building the sick person identity goes through the meaning of his/her narratives, and the way he/she narrates himself/herself will be the way he/she sees himself/herself. We can conclude by the participants' narratives, that the illness caused by the HIV virus interferes with daily events and thus, in their experiences as education professionals as they resignify their lives; on the other hand, the silencing promoted by the stigma that the disease carries makes it possible to understand the need for an education on sexuality that promotes understanding of the human being in its entirety and complexity.
Positive”narratives": lived experiences of teachers with HIV
Keywords: Vida de Professores - Adoecimento - HIV; Vida de Professores - HIV - Narrativas (auto)biográficas; Vida de Professores - Doença - Narrativas (auto)biográficas; Teachers’ Life - Sickness - HIV; Teachers’ Life - HIV - (auto)biographical narratives; Teachers’ Life - Disease - (auto)biographical narratives; CIENCIAS HUMANAS::EDUCACAO